A high-strength self-healing hydrogel and preparation method thereof
The slow healing speed of traditional hydrogels is solved by using hydrogen bond acceptors, hydrogen bond donors and crosslinking agents to generate deep eutectic solvents in self-healing hydrogels and adding β-cyclodextrin for polymerization. The problem of insufficient strength achieves a hydrogel with high hydrogen bond density and high compressive strength, which is suitable for load-bearing stress applications and reduces production costs and environmental impact.
Patent Information
- Application Number
- CN202210192916.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-01
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-03-01
AI Technical Summary
Traditional self-healing hydrogels have slow healing speed, harsh conditions and difficulty in having high healing rates and high strength, limiting their use in stress-bearing applications such as cartilage and tissue engineering scaffolds.
Hydrogen bond acceptor, hydrogen bond donor and crosslinking agent are mixed to form a deep eutectic solvent, and initiator and β-cyclodextrin are added for polymerization to form a hydrogel with high hydrogen bond density, which improves hydrocoagulation by this method. The self-healing rate and compressive strength of the glue.
A hydrogel with rapid healing and excellent mechanical properties has been achieved, increasing the self-healing rate and maximum compressive strength of the hydrogel, while reducing cost and environmental protection.
Smart Images

Figure CN114736392B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a self-healing hydrogel and a preparation method thereof. Background Art
[0002] Traditional self-healing hydrogels have slow healing speeds and harsh conditions, and most hydrogels cannot have both high healing rates and high strength. Low mechanical strength limits the pressure-bearing applications of self-healing hydrogels, and they cannot be used in stress-bearing applications such as cartilage and tissue engineering scaffolds. Hydrogels with high mechanical strength and low self-healing properties cannot heal in time when the material is damaged, reducing the life of the material.
[0003] The self-healing rate of hydrogels mainly depends on the dynamic bonds in the gel network. The dynamic bonds are mainly divided into dynamic non-covalent bonds and dynamic covalent bonds. The hydrogels constructed by dynamic non-covalent bonds have super high self-healing rates, but their mechanical strength is poor, and the prepared hydrogels cannot withstand pressure. The hydrogels constructed by dynamic covalent bonds have good mechanical properties, but the covalent bonds are strong, the bonding speed is slow, and reversible exchange can occur under certain conditions (such as light, heat, humidity stimulation, etc.), which reduces the self-healing rate of the hydrogel and slows down the healing speed.
[0004] At present, the methods of using deep eutectic solvents (DES) to prepare self-healing hydrogels to improve the healing speed of hydrogels are:
[0005] 1. Accelerate the healing process through external stimulation (such as magnetic field, pH, etc.);
[0006] 2. By changing the healing mechanism of the hydrogel (e.g., hydrophobic binding);
[0007] 3. Accelerate the diffusion of molecules in the hydrogel by artificially introducing a healing layer at the damaged site;
[0008] 4. Increase the contact area of the healing surface by reducing the stiffness of the hydrogel;
[0009] 5. Accelerate the diffusion of molecules in hydrogels by increasing the temperature of the healing environment
[0010] The above methods require a lot of effort, consume more raw materials, use complicated equipment and instruments, and are difficult to operate. How to use conventional raw materials and simple equipment to prepare hydrogels with high healing rate and high strength has become a technical problem that needs to be solved urgently. Summary of the invention
[0011] One of the purposes of the present invention is to provide a hydrogel that can heal quickly and has excellent mechanical properties; the second purpose of the present invention is to prepare a hydrogel with a high healing rate and high strength using a small amount of conventional drugs and simple equipment.
[0012] To achieve the above objectives, the following scheme is adopted:
[0013] A method for preparing a high-strength self-healing hydrogel comprises the following steps:
[0014] (1) mixing a hydrogen bond acceptor, a hydrogen bond donor and a cross-linking agent, and stirring the mixture at 70 to 100° C. until a transparent and clear liquid is obtained to obtain a deep eutectic solvent;
[0015] (2) adding an initiator and β-cyclodextrin to the obtained deep eutectic solvent at a temperature not lower than 35° C., and stirring to form a mixture solution; transferring the formed mixture solution to a tubular reactor, heating the reactor with a heat source to initiate a polymerization reaction, and then removing the heat source until the deep eutectic solvent liquid in the entire reactor is completely converted into a polymer gel;
[0016] (3) The obtained polymer gel is soaked and washed with distilled water, and then freeze-dried to obtain a β-cyclodextrin-filled hydrogel.
[0017] According to the above scheme, the hydrogen bond acceptor in step 1 is choline chloride.
[0018] According to the above scheme, the hydrogen bond donor in step 1 is a mixture of acrylamide and acrylic acid; the molar ratio of the two when mixed is 1:1.
[0019] According to the above scheme, the cross-linking agent in step 1 is one of N,N-methylenebisacrylamide divinylstyrene, polyethylene glycol dimethacrylate, 4,4'-dimethylacrylamidoazobenzene, and polyethylene glycol dimethacrylate.
[0020] According to the above scheme, the molar ratio of the hydrogen bond acceptor and hydrogen bond donor compounds in step 1 is 1:(2-3).
[0021] According to the above scheme, the amount of the cross-linking agent used in step 1 is 0.5-1.0% of the total mass of the deep eutectic solvent.
[0022] According to the above scheme, the initiator in step 2 is one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, dibenzoyl peroxide, and dodecanoyl peroxide; the amount used is 0.3-0.5% of the total mass of the deep eutectic solvent.
[0023] According to the above scheme, the amount of β-cyclodextrin used in step 2 is 0.2-2.0% of the total mass of the deep eutectic solvent.
[0024] According to the above scheme, in step 2, a heat source is used to heat the upper end or the lower end of the tubular reactor.
[0025] The present invention also provides a high-strength self-healing hydrogel, which is prepared by adopting the above scheme.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] 1. The present invention first mixes and heats a cross-linking agent (solid powder), a hydrogen bond donor compound (solid powder) and a hydrogen bond acceptor compound (solid powder) to obtain a stable, non-toxic room temperature deep eutectic solvent liquid, and then uses the room temperature deep eutectic solvent liquid as a monomer and medium for front-end polymerization to synthesize a filling hydrogel. The selected drugs are all solid and can evenly carry out the front-end polymerization reaction without the need for other liquid solvents to dissolve.
[0028] 2. The addition of β-cyclodextrin increases the hydrogen bond density in the hydrogel, greatly increases the bond exchange rate, and leads to an increase in the self-healing rate of the hydrogel. The present invention increases the hydrogen bond density in the hydrogel by adding fillers, increases the healing rate and healing speed of the hydrogel, and also increases the maximum compressive strength of the hydrogel.
[0029] 3. The prepared hydrogel is stable and non-toxic, and the remaining liquid after washing can be processed to obtain reusable choline chloride, which reduces costs and is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 : Self-healing curves of the hydrogels obtained in Examples 1-4 and Comparative Examples;
[0031] Figure 2 : Compression curves of the hydrogels obtained in Examples 1-4 and Comparative Examples. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] A method for preparing a high-strength self-healing hydrogel is provided in a specific embodiment:
[0034] (1) A hydrogen bond acceptor, a hydrogen bond donor and a cross-linking agent are mixed and stirred at 70 to 100° C. until a transparent and clear liquid is obtained to obtain a deep eutectic solvent; a cross-linking agent (solid powder), a hydrogen bond donor compound (solid powder) and a hydrogen bond acceptor compound (solid powder) are mixed and heated to obtain a stable, non-toxic room temperature deep eutectic solvent liquid, and then the room temperature deep eutectic solvent liquid is used as a monomer and medium for front-end polymerization to synthesize a filling hydrogel. The selected drugs are all solid and can evenly carry out the front-end polymerization reaction without the need for other liquid solvents to dissolve.
[0035] (2) Adding an initiator and β-cyclodextrin to the obtained deep eutectic solvent at a temperature not lower than 35°C, stirring evenly to form a mixture solution; transferring the formed mixture solution to a tubular reactor, heating the reactor with a heat source to initiate a polymerization reaction, and then removing the heat source until the deep eutectic solvent liquid in the entire reactor is completely converted into a polymer gel; adding β-cyclodextrin increases the hydrogen bond density in the hydrogel, greatly increases the bond exchange rate, and leads to an increase in the self-healing rate of the hydrogel. The present invention increases the hydrogen bond density in the hydrogel by adding fillers, which increases the healing rate and healing speed of the hydrogel while also increasing the maximum compressive strength of the hydrogel.
[0036] (3) The obtained polymer gel is soaked and washed with distilled water, and then freeze-dried to obtain a hydrogel filled with β-cyclodextrin; the prepared hydrogel is stable and non-toxic, and the remaining liquid after washing can be processed to obtain reusable choline chloride, which reduces costs and is green and environmentally friendly.
[0037] In a specific implementation manner, the selection of each raw material is as follows:
[0038] The hydrogen bond acceptor used was choline chloride.
[0039] The hydrogen bond donor is a mixture of acrylamide and acrylic acid; the molar ratio of the two when mixed is 1:1.
[0040] The self-healing of the high-strength hydrogel of the present invention is mainly achieved through the dynamic reversible behavior of hydrogen bonds between molecular chains, and the formation of hydrogen bonds comes from the carboxyl groups in acrylamide and the hydroxyl groups in acrylic acid, both of which are indispensable.
[0041] The crosslinking agent is N,N-methylenebisacrylamide divinyl styrene, polyethylene glycol dimethacrylate, 4,4'-dimethylacrylamidoazobenzene or polyethylene glycol dimethacrylate; the amount of the crosslinking agent is 0.5-1.0% of the total mass of the deep eutectic solvent.
[0042] Optimally, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor compound is 1:(2-3).
[0043] The initiator is potassium persulfate, ammonium persulfate, azobisisobutyronitrile, dibenzoyl peroxide or dodecyl peroxide; the dosage is 0.3-0.5% of the total mass of the deep eutectic solvent.
[0044] The amount of β-cyclodextrin used is 0.2-2.0% of the total mass of the deep eutectic solvent.
[0045] Optimally, a heat source is used to heat the upper end or the lower end of the tubular reactor.
[0046] Accordingly, a self-healing hydrogel with both high healing rate and high strength is obtained in the specific embodiment.
[0047] Embodiment 1 (FP1):
[0048] (1) 2.132 g of acrylamide, 4.189 g of choline chloride, 2.162 g of acrylic acid, and 0.085 g of N,N-methylenebisacrylamide were mixed and stirred in an oil bath at 70° C. until a transparent and clear liquid was formed, and then allowed to stand and cool to room temperature to obtain a room temperature deep eutectic solvent liquid;
[0049] (2) adding 0.043 g potassium persulfate and 0.022 g β-cyclodextrin to the room temperature deep eutectic solvent liquid obtained in step (1) in sequence to form a mixture solution, then transferring the formed mixture solution into a test tube, heating the upper end of the reactor with an electric soldering iron to decompose the initiator by heat to initiate the reaction, and removing the heat source after the thermal initiation reaction starts until all the raw materials in the reactor are converted into polymer gel;
[0050] (3) The polymer gel obtained in step (2) is soaked and washed with distilled water to remove choline chloride, and the polymer gel after soaking and washing is then freeze-dried to obtain the target β-cyclodextrin hydrogel, wherein the hydrogel is light yellow.
[0051] According to measurement, the healing rate of this embodiment after healing for 48 hours is 79.41%, and the maximum compressive strength is 24.20 MPa.
[0052] Embodiment 2 (FP2):
[0053] (1) 2.132 g of acrylamide, 4.189 g of choline chloride, 2.162 g of acrylic acid, and 0.085 g of N,N-methylenebisacrylamide were mixed and stirred in an oil bath at 70° C. until a transparent and clear liquid was formed, and then allowed to stand and cool to room temperature to obtain a room temperature deep eutectic solvent liquid;
[0054] (2) adding 0.043 g potassium persulfate and 0.043 g β-cyclodextrin to the room temperature deep eutectic solvent liquid obtained in step (1) in sequence to form a mixture solution, and then transferring the formed mixture solution into a test tube, heating the upper end of the reactor with an electric soldering iron to decompose the initiator by heat to initiate the reaction, and after the thermal initiation reaction begins, removing the heat source until all the raw materials in the reactor are converted into polymer gel;
[0055] (3) The polymer gel obtained in step (2) is soaked and washed with distilled water to remove choline chloride, and the polymer gel after soaking and washing is then freeze-dried to obtain the target β-cyclodextrin hydrogel, wherein the hydrogel is light yellow.
[0056] According to measurement, the healing rate of this embodiment after healing for 48 hours is 81.75%, and the maximum compressive strength is 35.44 MPa.
[0057] Embodiment 3 (FP3):
[0058] (1) 2.132 g of acrylamide, 4.189 g of choline chloride, 2.162 g of acrylic acid, and 0.085 g of N,N-methylenebisacrylamide were mixed and stirred in an oil bath at 70° C. until a transparent and clear liquid was formed, and then allowed to stand and cool to room temperature to obtain a room temperature deep eutectic solvent liquid;
[0059] (2) adding 0.043 g potassium persulfate and 0.087 g β-cyclodextrin to the room temperature deep eutectic solvent liquid obtained in step (1) in sequence to form a mixture solution, and then transferring the formed mixture solution into a test tube, heating the upper end of the reactor with an electric soldering iron to decompose the initiator by heat to initiate the reaction, and after the thermal initiation reaction begins, removing the heat source until all the raw materials in the reactor are converted into polymer gel;
[0060] (3) The polymer gel obtained in step (2) is soaked and washed with distilled water to remove choline chloride, and the polymer gel after soaking and washing is then freeze-dried to obtain the target β-cyclodextrin hydrogel, wherein the hydrogel is light yellow.
[0061] According to measurement, the healing rate of this embodiment after healing for 48 hours is 87.00%, and the maximum compressive strength is 38.78 MPa.
[0062] Embodiment 4 (FP4):
[0063] (1) 2.132 g of acrylamide, 4.189 g of choline chloride, 2.162 g of acrylic acid, and 0.085 g of N,N-methylenebisacrylamide were mixed and stirred in an oil bath at 70° C. until a transparent and clear liquid was formed, and then allowed to stand and cool to room temperature to obtain a room temperature deep eutectic solvent liquid;
[0064] (2) adding 0.043 g potassium persulfate and 0.176 g β-cyclodextrin to the room temperature deep co-solvent liquid obtained in step (1) in sequence to form a mixture solution, and then transferring the formed mixture solution into a test tube, heating the upper end of the reactor with an electric soldering iron to decompose the initiator by heat to initiate the reaction. After the thermal initiation reaction begins, the heat source is removed until all the raw materials in the reactor are converted into polymer gel;
[0065] (3) The polymer gel obtained in step (2) is soaked and washed with distilled water to remove choline chloride, and the polymer gel after soaking and washing is then freeze-dried to obtain the target β-cyclodextrin hydrogel, wherein the hydrogel is light yellow.
[0066] According to measurement, the healing rate of this embodiment after 48 hours of healing is 91.67%, and the maximum compressive strength is 44.88 MPa.
[0067] Comparative Example (FP0):
[0068] (1) 2.132 g of acrylamide, 4.189 g of choline chloride, 2.162 g of acrylic acid, and 0.085 g of N,N-methylenebisacrylamide were mixed and stirred in an oil bath at 70° C. until a transparent and clear liquid was formed, and then allowed to stand and cool to room temperature to obtain a room temperature deep eutectic solvent liquid;
[0069] (2) adding 0.043 g of potassium persulfate to the room temperature deep eutectic solvent liquid obtained in step (1) to form a mixture solution, then transferring the formed mixture solution into a test tube, heating the upper end of the reactor with an electric soldering iron to decompose the initiator by heat to initiate the reaction, and removing the heat source after the thermal initiation reaction begins until all the raw materials in the reactor are converted into polymer gel;
[0070] (3) The polymer gel obtained in step (2) is soaked and washed with distilled water to remove choline chloride, and the polymer gel after soaking and washing is then freeze-dried to obtain the target β-cyclodextrin hydrogel, wherein the hydrogel is light yellow.
[0071] According to measurement, the healing rate of this embodiment after 48 hours of healing is 64.85%, and the maximum compressive strength is 19.85 MPa.
[0072] The raw material dosage and product characterization of Examples 1-4 and Comparative Example 1 are shown in Table 1; wherein the characterization and test methods of the 48h healing rate and the maximum compressive strength are as follows:
[0073] The prepared hydrogel was cut into two sections, and the cross sections of the hydrogel were overlapped. After being placed for a period of time without any external intervention, the tensile properties of the healed hydrogel samples were tested using a microcomputer-controlled electronic universal testing machine. The tensile speed was set to 100 mm / min and the original gauge length was 50 mm. The self-healing rate of the hydrogel was calculated as follows:
[0074]
[0075] Where P0 is the maximum tensile strength of the uncut hydrogel, P t is the maximum tensile strength of the hydrogel after healing time t.
[0076] Compression properties test of hydrogel
[0077] The hydrogel was subjected to compression test using the TA.XTC-18 texture analyzer from Shanghai Baosheng Company. Before the test, the hydrogel was cut into small cylinders with a diameter of 10 mm and a length of 10 mm. The compression head was compressed downward at a speed of 3 mm / min until the hydrogel deformation reached 80%. The formula for calculating the compressive strength of the hydrogel is as follows:
[0078]
[0079] where F is the applied force and S is the surface area of the hydrogel.
[0080] Table 1
[0081]
[0082] As shown in Table 1, with the increase of the amount of β-cyclodextrin, the 48h healing rate and the maximum compressive strength of the obtained self-healing hydrogel increased significantly. The 48h healing rate and the maximum compressive strength of the self-healing hydrogel obtained without adding β-cyclodextrin were obviously inferior.
[0083] The self-healing curves of the hydrogels obtained in Examples 1-4 and Comparative Examples are shown in the attached Figure 1 As shown, with the increase of β-cyclodextrin content, the healing rate and healing speed of the hydrogel showed an upward trend.
[0084] The compression curves of the hydrogels obtained in Examples 1-4 and Comparative Examples are shown in the attached figure. Figure 2 As shown in the figure, the maximum compressive strength of the hydrogel increased significantly with the increase of β-cyclodextrin content.
Claims
1. A method for preparing a high-strength self-healing hydrogel, characterized in that The steps include: (1) mixing a hydrogen bond acceptor, a hydrogen bond donor and a cross-linking agent, and stirring them at 70 to 100° C. until a transparent and clear liquid is obtained to obtain a deep eutectic solvent, wherein the hydrogen bond acceptor is choline chloride, and the hydrogen bond donor is a mixture of acrylamide and acrylic acid; (2) adding an initiator and β-cyclodextrin to the obtained deep eutectic solvent at a temperature not lower than 35° C., and stirring to form a mixture solution; transferring the formed mixture solution to a tubular reactor, heating the reactor with a heat source to initiate a polymerization reaction, and then removing the heat source until the deep eutectic solvent liquid in the entire reactor is completely converted into a polymer gel; the amount of β-cyclodextrin used is 0.2 to 2.0% of the total mass of the deep eutectic solvent; (3) The obtained polymer gel is soaked and washed with distilled water, and then freeze-dried to obtain a β-cyclodextrin-filled hydrogel.
2. The method for preparing the high-strength self-healing hydrogel according to claim 1, characterized in that In step 1, the molar ratio of acrylamide and acrylic acid when mixed is 1:
1.
3. The method for preparing the high-strength self-healing hydrogel according to claim 1, characterized in that The cross-linking agent in step 1 is one of N, N-methylenebisacrylamide, polyethylene glycol dimethacrylate, 4,4'-dimethylacrylamidoazobenzene, and polyethylene glycol dimethacrylate.
4. The method for preparing the high-strength self-healing hydrogel according to claim 1, characterized in that In step 1, the molar ratio of the hydrogen bond acceptor and the hydrogen bond donor compound is 1:(2-3).
5. The method for preparing the high-strength self-healing hydrogel according to claim 1, characterized in that The amount of the cross-linking agent used in step 1 is 0.5 to 1.0% of the total mass of the deep eutectic solvent.
6. The method for preparing the high-strength self-healing hydrogel according to claim 1, characterized in that The initiator in step 2 is one of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, dibenzoyl peroxide, and dodecanoyl peroxide.
7. The method for preparing the high-strength self-healing hydrogel according to claim 1, characterized in that The amount of the initiator used in step 2 is 0.3 to 0.5% of the total mass of the deep eutectic solvent.
8. The method for preparing the high-strength self-healing hydrogel according to claim 1, characterized in that In step 2, a heat source is used to heat the upper end or the lower end of the tubular reactor.
Citation Information
Patent Citations
Method for preparing conductive polysaccharide compound hydrogel by adopting front-end polymerization of polysaccharide eutectic solvent mixture solution
CN112876611A
Hydrogel filled with nitrogen-doped carbon nanotubes and preparation method of hydrogel
CN113307909A